(untitled) (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2026)
Slang is a type of language variation that is widely employed by teenagers as a means of expressing personal identity, fostering group solidarity, and demonstrating linguistic creativity. Its use is not confined to everyday spoken interactions but is also frequently depicted in popular media, such as comics, which reflect teenage language practices in social contexts. This study aims to examine the use of slang in Archie Comics as a representation of teen slang. A descriptive qualitative approach was adopted, with data derived from character dialogues in Archie Comics. The data were collected through documentation techniques by identifying and recording slang words and phrases. The analysis involved classifying the types of slang and interpreting their functions based on sociolinguistic theories. The results indicate that Archie Comics contain various forms of slang, including clipping, acronyms, blending, and semantic shifts. These slang expressions function to create informal interactions, convey emotional expressions, and reinforce teenage identity. Thus, Archie Comics can be regarded as an effective medium for authentically representing teen slang.